The Influence of Service Quality, Product Diversity and Prices on Purchase Decisions at Rizky Store in Bireuen District, Aceh Province - Sutoyo Sutoyo; Zuriani Ritonga; Chairul Bariah (Budapest International Research and Critics University, 2022)
This study aims to determineInfluenceQuality of Service, Diversity of Products and Prices on Purchase Decisions at Rizky Stores in Bireuen Regency, Aceh Province. Data collection in this study was conducted through an interview approach with a quantitative descriptive type of research by distributing questionnaires to 96 people. Data collection techniques were carried out by interviews and questionnaires. The data analysis tool used in this study uses SPSS (Statistical Product Software Solution). Data analysis in this study is instrument test, multiple linear regression analysis, hypothesis testing using partial significant test (t test) and simultaneous significant test (F test). The results of this study indicate that partially (t test) it is known thatService qualitypositive and significant effect onBuying decision. VariableProduct Diversitypositive and significant effect onBuying decision. Then VariablePricepositive and significant effect onBuying decision At Rizky's Shop in Bireuen Regency, Aceh Province. In the simultaneous test (F test) it is known thatQuality of Service, Diversity of Products and Pricespositive and significant effect onBuying decision At Rizky's Shop in Bireuen Regency, Aceh Province.